The effects of cold water immersion on anaerobic power, dynamic balance and muscle activation after a karate kumite fighting in female karateka - Nezhad, T. A.; Faghihi, S.; Hazrati, A.; Bahrami, K. (International Journal of Applied Exercise Physiology, 2017)
Many athletes are using specific techniques to minimize fatigue and accelerate recovery processes. Cold water immersion (CWI) is one of the most popular interventions used by athletes to potentially return to their pre-fatigue performance level. the purpose of this study was to investigate the effects of CWI on anaerobic performance, balance and muscle activation of female karateka after a simulated match. 15 young female karateka (age: 18.7±1.7 years, body mass: 55.5±6.3 kg, height:165±5.1 cm) with at least three years' experience in karate kumite fighting were included in the study. After three round 3-minute competition, participants were grouped into a CWI group (20 min at 12±1°C) and a control group (CTL). Anaerobic power (30 s Wingate test), and dynamic balance (Star-Excursion test) were measured before the competition and 24 h after intervention. Surface electromyography (EMG) was sampled from quadriceps femoris muscles. Peak normalized muscle activation levels and force were identified during maximal isometric test. A significant decrease in the anaerobic performance after the competition was observed for both groups (p<0.05). CWI were effective in enhancing the anaerobic performance after competition compared with the CTL. Dynamic balance decreased for two groups, although CWI resulted in the smallest reduction in balance. There was a significant difference in peak and mean RMS values of the EMG in Rectus Femoris but not Vastus muscles after the CWI intervention when compared to CTL (p<0.05). CWI improve recovery related to dynamic balance and anaerobic performance of karate kumite fighter. It can be concluded that CWI appears to promote muscle activation and reduce fatigue that is related to better performance in 24 hours post intervention.